Measuring Health Promoter Core Competencies Among Graduate Students Enrolled in a Health Promotion Course - Lauren M. Sherk; Melissa MacKay; Jennifer E. McWhirter; Andrew Papadopoulos (Canadian Journal for the Scholarship of Teaching and Learning)
Global public health events such as the COVID-19 pandemic create public awareness of the need for skilled public health graduates and public health graduate programs. Core Competencies for Public Health are tools that can guide graduate-level public health programs to ensure students are receiving the appropriate knowledge, tools and skills required to become effective public health practitioners that comprise a strong public health workforce. Case-based learning is a learner centered approach that allows students to apply their knowledge to real-world scenarios, promoting higher-order thinking. The University of Guelph Master of Public Health graduate program incorporates both the Core Competencies for Public Health in Canada as created by the Public Health Agency of Canada and the Pan-Canadian Health Promoter Competencies developed by Health Promotion Canada (HPC), as well as experiential learning to ensure students are receiving a high-quality learning experience throughout the course of their studies. Assessments of the program, individual courses within the program, and assignments within the courses are beneficial to ensure alignment with the Public Health Core Competencies—including Health Promotion Core Competencies. In the present study, surveys were administered to students enrolled in the University of Guelph Winter 2021 semester Health Promotion class before and after completion of an experiential group health promotion assignment worth 50% of their grade. The assignment used case-based learning within a group setting, allowing students to engage and apply knowledge gained through the semester to solve a real-world public health issue. Students reported increased self-perceived proficiency in all Core Competencies after completion of the practice-based group health promotion program assessment.